(untitled) (ADMPG Journal, 2021)
COVID-19 pandemic has affected organizations as a whole, be it public or private ones. In this background, educational organizations have been considerably impacted by the changes brought by the pandemic, adjusting sanitary security norms, adapting workspaces, looking for partnerships and technologies to support new virtual environment models. So, this research aims to comprehend how decision-makers’ managerial capabilities have influenced current action strategies facing pandemic so as to guarantee the professionalizing and technical formation program by the government of the State of Ceará, Brazil. To do so, interviews were held with managers inside a Professional Education Coordination, associated to a documental research, taking works focused upon the approaches to Microfoundations theories and Strategy as Practice as its reference, which would relate these theories with the performance of the strategical changes made at the organizations. This study found that managerial capabilities, when potentialized by modern managerial strategies, chiefly by the continuous improvement of managers and their subordinates, represents an important source to face troubled contexts and instability scenarios.